Features of modernity in the collection of the rain song - Al-Jarah, Mona Bashir (Journal of Humanities & Social Sciences, 2017)
Al- Sayyab demonstrated in the group: "Rain Song" clear versatile in his poetic methods in at all language, Imaginary and percussion levels. The researcher revealed Linguistic formations lines, and Its Impact semantic associated with space places up and down attached two addendums contain the places names scheduling, the first represents: the upward trend of semantics, and its tends associated with the village, while the second represents the landing trend, in contrast to its predecessor, and associated with city on spatial level. The picture in that group Al-Sayyab crowd many of religious symbols, mythical, historical, he has tended his symbols to clear oriented abstract, blend self-Bmoduaa and blending. Despite the large number of overlaps symbols, and the momentum of their voices discordant and responsive to, and must through it integrative scene those conflicting, both; however, the propensity with symbol to abstraction prevented dramatic completeness of the substantive dimensions that require to complete the structural frameworks elements of anthropomorphism, and real voices graduated to come into the existential scene, as well as control features a dramatic monologue but not help us to judgment the existence of a clear manifestation of a dramatic fall within the requirements calling for materializing the event. In the final level of this research I found out after my studies of rhythmic poem in the Sayyab lattice, or rhythm of plastic threaded in the core structure of the poem in the group: "Rain Song" contributed to raising the productive capacity of the semantics of the poem and the development of the intellectual trends poet through various voices acoustic and signed rhythmic and its mingled rhythm in internal experience that the poems are arranged in a group as a whole: "Rain Song”.